Dosis facit venenum - R. N. Alyautdin R.N; B. K. Romanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
The article presents the history of the exploration of arrow poisons, used in Asia, Africa and South America. The active ingredients of these poisonswere widely used and continue to apply currently in traditional and official medicine. Methodology for development of new drugs based on arrow poisons has determined tendencies of drug design in modern pharmacology.